EFEKTIFITAS EKSTRAK PUNICA GRANATUM TERHADAP KADAR NITRICT OXYDE PADA KULTUR HUVECS YANG DIPAPAR PLASMA PREEKLAMPSI - Megawati Megawati; Januarsih Januarsih; Fitria Jannatul Laili (Jurnal_Kebidanan, 2025)
Preeclampsia is one of the leading causes of maternal morbidity and mortality, with pathogenesis involving oxidative stress due to increased free radicals and decreased antioxidant activity. Red pomegranate (Punica granatum) contains polyphenols, anthocyanins, and tannins, which act as natural antioxidants. This study aimed to investigate the effect of Punica granatum extract on Nitric Oxide (NO) levels in Human Umbilical Vein Endothelial Cells (HUVECs) exposed to preeclampsia plasma. An experimental study with a post-test only control group design was conducted with five groups: negative control (HUVECs + normal plasma), positive control (HUVECs + preeclampsia plasma), and three treatment groups with Punica granatum extract at 14 ppm, 28 ppm, and 56 ppm. NO levels were measured using the ELISA method after 24 hours of incubation. The results showed significant differences among groups (p < 0.05). The 56 ppm extract dose resulted in the most significant decrease in NO levels (20.3 µM), comparable to the normal control group (18.4 µM). This study is at TRL 3–4, representing a proof-of-concept based on in vitro testing. In conclusion, Punica granatum extract has potential as a natural antioxidant and a complementary therapy candidate for preeclampsia, although further studies in animal models and clinical trials are required.